In Vivo Magnetic Resonance Imaging of Type I Collagen Scaffold in Rat: Improving Visualization of Bladder and Subcutaneous Implants - Sun, Yi (Tissue Eng Part C Methods, 2014)
Noninvasive monitoring of implanted scaffolds is important to understand their behavior and role in tissue engineering, in particular to follow their degradation and interaction with host tissue. Magnetic resonance imaging (MRI) is well suited for this goal, but its application is often hampered by the low contrast of scaffolds that are prepared from biomaterials such as type I collagen. The aim of this study was to test iron oxide particles incorporation in improving their MRI contrasts, and to follow their degradation and tissue interactions. Scaffolds with and without iron oxide particles were implanted either subcutaneously or on the bladder of rats. At predetermined time points, in vivo MRI were obtained and tissues were then harvested for histology analysis and transmission electron microscopy. The result showed that the incorporation of iron oxide particles improved MRI contrast of the implants, providing information on their location, shapes, and degradation. Second, the host tissue reaction to the type I collagen implants could be observed in both MRI and histology. Finally, MRI also revealed that the degradation and host tissue reaction of iron particles-loaded scaffolds differed between subcutaneous and bladder implantation, which was substantiated by histology.